2007
DOI: 10.1016/j.yqres.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Paleoceanographic evolution of the SW Svalbard margin (76°N) since 20,000 14C yr BP

Abstract: Two cores from the southwestern shelf and slope of Storfjorden, Svalbard, taken at 389 m and 1485 m water depth have been analyzed for benthic and planktic foraminifera, oxygen isotopes, and ice-rafted debris. The results show that over the last 20,000 yr, Atlantic water has been continuously present on the southwestern Svalbard shelf. However, from 15,000 to 10,000 14C yr BP, comprising the Heinrich event H1 interval, the Bølling–Allerød interstades and the Younger Dryas stade, it flowed as a subsurface water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
309
3
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(350 citation statements)
references
References 109 publications
32
309
3
6
Order By: Relevance
“…1). The outflows during MIS 3 can probably best be compared with the outflow during the Bølling interstadial at the beginning of the deglaciation c. 14.5 kyr BP, when a 10 cm to more than 2 m thick laminated bed was deposited along the western margin of Svalbard over a time span of less than 400 years 23,24,28,33 , which is comparable to the estimated duration of the melting events during MIS 3 (see above). The bed is found at distances from the ice margin that are comparable to the distance from our core site to the ice margin during MIS 3.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…1). The outflows during MIS 3 can probably best be compared with the outflow during the Bølling interstadial at the beginning of the deglaciation c. 14.5 kyr BP, when a 10 cm to more than 2 m thick laminated bed was deposited along the western margin of Svalbard over a time span of less than 400 years 23,24,28,33 , which is comparable to the estimated duration of the melting events during MIS 3 (see above). The bed is found at distances from the ice margin that are comparable to the distance from our core site to the ice margin during MIS 3.…”
Section: Discussionmentioning
confidence: 69%
“…However, it is more likely that the differences are primarily caused by frequent changes in sedimentation rate. Several studies have shown that the sedimentation rate on the Svalbard margin was low during Heinrich event H1 and very high during the following Bølling interstadial 13,[22][23][24][25] . It seems probable that similar differences occurred between the stadials and interstadials studied here.…”
Section: Resultsmentioning
confidence: 99%
“…For the last glacial period, the huge 'Fleuve Manche' discharges dating from ca. 18 ka correlate with significant freshwater fluxes from the circum-North Atlantic ice sheets, as reported from the FIS (Kleiber et al, 2000;Dahlgren and Vorren, 2003;Lekens et al, 2005;Rasmussen et al, 2007), the BIIS (Zaragosi et al, 2001;Hall et al, 2006;Ménot et al, 2006;Toucanne et al, 2008) and the LIS (Clarke et al, 1999;Tripsanas and Piper, 2008), indicating that the 'Fleuve Manche' activity reflected a large-scale event of meltwater releases. Geochemical and isotopical data from numerous cores from the North Atlantic show a sharp concomitant decrease in the rate of deep-water formation leading to the HE 1 and a collapsed THC until ca.…”
Section: Comments On the Timing Of Major 'Fleuve Manche' Discharges Amentioning
confidence: 71%
“…Several studies record a cooling in the late Holocene in both the bottom (Ślubowska-Woldengen et al, 2007;Risebrobakken et al, 2010) and surface water masses (Voronina et al, 2001;Hald et al, 2007;Rasmussen et al, 2007;Risebrobakken et al, 2010), which could be related to declining summer insolation (Berger and Loutre, 1991) or displacements of Arctic and polar water masses (Hald et al, 2007). Opposite to this cooling, two high-resolution studies from Bear Island and the western and northern Svalbard shelf (Jernas et al, 2013) infer a warming over the last ∼ 200 yr induced by the renewed inflow of Atlantic water.…”
Section: E Groot Et Al: Reconstruction Of Atlantic Water Variabimentioning
confidence: 99%